A dynamic view of local knowledge and epistemic bonds to place: Implications for senses of place and the governance of biodiversity conservation - Castro, P. (Changing senses of place: Navigating global challenges, 2021)
bstract People’s relations to place are crucially relevant for their engagement with, or resistance to, measures adopted in view of biodiversity conservation. Today, a considerable share of such measures are legal ones. Many are supranational legal orders: originating in multi-country agreements that are transposed into national legal frameworks, becoming then laws to be implemented at the local level. This chapter focuses on one such supranational legal order, the one governing EU ‘Natura 2000’ protected sites. It explores Natura’s legal-local relational dynamics - where laws affect people-place relations, and those relations affect the reception of the laws - by focusing on how two groups directly impacted by Natura laws: farmers and artisanal fishers. It presents a dynamic perspective in which epistemic labour – i.e. knowledge as process, not just content (Maranta et al., 2003) – takes a central role, and argues that a better understanding of these dynamic requires reconceptualising people-place relations in a way that is more attentive to the epistemic dimension, i.e. to local knowledge and epistemic bonds to place. This perspective also posits that meaning and knowledge, although interdependent, are not the same. The perspective is illustrated with examples of how fishers and farmers living in Natura 2000 sites discuss their places, knowledges and laws. The chapter thus shows how by including the epistemic dimension, the conceptualisation of senses of place can become more relational, plural and dynamic, allowing us to understand people’s engagement with place through three dimensions: engagement through meaning, resulting in belonging and identity bonds; engagement through affection, resulting in attachment; and engagement through knowledge, resulting in epistemic bonds.